Social Skills Training For Future Leaders: Nurturing Social Awareness Through Kampus Mengajar Program - Intani, Zahra Frida; Kearens, Heggy; Sari, Diyan Purnama (Journal of Leadership in Organizations, 2024)
Introduction/Main Objectives: This paper examines the Kampus Mengajar (KM) program, a government initiative aimed at addressing learning loss among primary students in Indonesia due to the COVID-19 pandemic while enhancing the soft skills of college students by giving them teaching experience in schools. Background Problems: The issues investigated in this study are how Kampus Mengajar facilitates the development of social awareness and social responsibility among its participants and its relation to leadership potential. Novelty: This paper analyses the Kampus Mengajar program, its impact on developing social awareness and social responsibility, and its correlation with leadership potential among its participants. While the previous batch focused on its impact in addressing learning loss, more research needs to be done on its potential to enhance socioemotional skills. Research Methods: The research method used in this paper is a qualitative analysis of survey data as primary data and a monitoring report as secondary. The data were analysed using thematic analysis to identify keys related to social awareness and social responsibility themes. Finding/Results: The empirical findings suggest that while Kampus Mengajar does facilitate the development of social awareness among its participants, it may not necessarily facilitate social responsibility. Conclusion: The study concludes that Kampus Mengajar facilitates the development of social awareness among its participants but may need to be supplemented with additional interventions to enhance social responsibility. This study has also indicated that implementing socio-emotional learning at schools, which facilitates social awareness, has increased participants' leadership potential.